Learning from the historic city: architectural heritage rehabilitation and GIS, the URS-Viseu novo (Portugal) legacy - Martins, Ana Maria Tavares (2020)
All cities share a similar challenge: "How to rehabilitate the historic centre without denigrating its identity and at the same time encourage private investment in built cultural heritage in order to avoid its degradation?" The historic centres are the oldest and most central areas of the cities, defining their identity, but have fallen into economic, social and residential decay, in part by the abandonment and aging of their most outstanding buildings. The presented paper intends to study the projects promoted by the Portuguese Municipality of Viseu, namely through the Urban Rehabilitation Society Viseu Novo, in short URS Viseu Novo. This revitalization strategy of the Historic Centre of Viseu aims to identify the buildings’ most relevant problems, the rehabilitation’s proposed objectives and the feasible solutions to renovate them promoting youth housing, cultural events and others. A contextualization analysis of the URS's work in the historic area of Viseu is presented through the inventory of its interventions using Geographic Information Systems (GIS). GIS spatial analyses, syntheses and conclusions can be used for the presentation of rehabilitation solutions duly framed in the goals and environment intended for these noble areas. As a result of this work, and starting from this principle, another research is being developed and serves as theme for the Integrated Master in Architecture Dissertations, highlighting the relevance and pertinence of this theme.